2021
DOI: 10.1111/jmcb.12769
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differences in Household Debt across the United States and Euro Area Countries

Abstract: United States and Euro Area Countries Household debt has played a central role in the global financial crisis, yet our understanding of it remains limited. We put U.S. household leverage in an international perspective, using household-level data for the United States and 10 euro area economies. U.S. households have the highest prevalence of mortgage and consumer debt, hold comparatively large amounts and face higher debt burdens despite having higher income. We find that the U.S. economic environment is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Second, the task in the original experiment is complex, so reproducing the original results will help establish a reliable experimental design to study debt aversion. Thirdly, Meissner (2016) uses a sample of the student population in Germany, a country which -by international standards -is known for moderate levels of household debt (e.g., Christelis et al, 2021), an excessive reliance on cash payments (e.g., von Kalckreuth et al, 2014;Bagnall et al, 2016), and low tuition fees for higher 1 For an extensive survey of laboratory experiments on dynamic stochastic optimization problems see Duffy (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the task in the original experiment is complex, so reproducing the original results will help establish a reliable experimental design to study debt aversion. Thirdly, Meissner (2016) uses a sample of the student population in Germany, a country which -by international standards -is known for moderate levels of household debt (e.g., Christelis et al, 2021), an excessive reliance on cash payments (e.g., von Kalckreuth et al, 2014;Bagnall et al, 2016), and low tuition fees for higher 1 For an extensive survey of laboratory experiments on dynamic stochastic optimization problems see Duffy (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, we found it necessary to include country dummy variables as they may capture a contextual effect once the household's characteristics are considered. Additionally, some studies report that household debt holding differ substantially across countries, as well as the burden that these debts impose (Christelis et al, 2015).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…For instance, studying identical twins, Cronqvist and Siegel (2015) found that the decision how much to save out of one's current income can be traced to shared genes. Moreover, Barth, Papageorge, and Thom (2020) Two illustrative papers promoting explanations for portfolio heterogeneity based on institutional variation are Christelis, Georgarakos, and Haliassos (2013) and Christelis, Ehrmann, and Georgarakos (2017). Focusing on the portfolios of older households in the United States and selected European countries, they apply a counterfactual method to investigate cross-country variation in the amount and types of assets and liabilities households chose to accumulate during their lifetimes.…”
Section: Theories Of Portfolio Heterogeneitymentioning
confidence: 99%